The conus artery as a lethee in coronary artery disease - Yurtdaş, Mustafa; Doğan, Zeki (Acta Medica, 2025)
Collaterals connecting coronary arteries may protect the heart from ischemic attacks, thus mediate in the preservation of myocardial functions. Symptoms and ventricular functions are closely related to the quality of coronary collaterals. In the presence of chronic total occlusion (CTO) in the left anterior descending artery (LAD), collateral circulation from the conus artery to the LAD is rare but may be life-saving. We report a 44-year-old patient with moderate left ventricular dysfunction and multi-vessel coronary disease in whom collateral flow was supplied by the conus artery, connecting to distal to the LAD CTO.